Socio-Economic Impacts of Endemic and Epidemic Diseases on Livestock Production Systems in Tanzania - Chacha, John (Journal of Animal Health, 2024)
Purpose: The aim of the study was to examine socio-economic impacts of endemic and epidemic diseases on livestock production systems in Tanzania. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The study revealed that endemic diseases such as brucellosis, foot-and-mouth disease (FMD), and contagious caprine pleuropneumonia (CCPP) pose ongoing challenges to livestock health, productivity, and household livelihoods. Epidemic diseases like avian influenza and peste des petits ruminants (PPR) can cause sudden outbreaks, leading to acute disruptions in production and trade. These disease outbreaks result in various socio-economic consequences, including decreased livestock productivity, loss of income for farmers, increased veterinary and containment costs, and disruptions in domestic and international trade. Additionally, diseases can exacerbate poverty and food insecurity among rural communities reliant on livestock for sustenance and income generation. Unique Contribution to Theory, Practice and Policy: Economic theory of disease control & social-ecological systems theory may be used to anchor future studies on socio-economic impacts of endemic and epidemic diseases on livestock production systems in Tanzania. Building technical capacity at the grassroots level empowers communities to implement effective disease management strategies and adopt biosecurity measures. Establishing community-based disease surveillance systems that empower local communities to monitor and report disease outbreaks in livestock populations. Providing financial support and risk-sharing mechanisms mitigate economic losses and encourage proactive disease management practices. Establish data-sharing mechanisms and surveillance networks that facilitate real-time exchange of information on disease outbreaks, epidemiological trends, and economic impacts.